2013
DOI: 10.4236/nm.2013.42015
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Rhythms Response to 10 Hz Flicker Is Wavelength Dependent

Abstract: Since Adrian and Metthew [1], light may be considered the dominant stimulus for the brain. This statement is confirmed after the discovery of the suprachiasmatic nucleus (SCN) that regulates the master biological clock [2]. In 1998 the discovery of photopigment melanopsin in the ganglion cells of the retina, give new insight in the importance of the light in the pathophysiology of the brain [3]. We have studied the effect of flashing at 10 Hz with LED light of different wavelength on the response of the alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…H. Sakamoto and co-workers showed that intermittent photic stimulation at 10 Hz could externally induce a coherent state in the cortex and persist as a form of short memory [19]. Milone's group showed that a 10 Hz red light-emitting diode (650 nm) light, consistent with the alpha rhythms, gives rise to cognitive function and regulatory function in the brain [20]. Specific brainwaves and functions of the brain can be induced with different kinds of light stimulations.…”
Section: Light Stimulation and Eegmentioning
confidence: 99%
“…H. Sakamoto and co-workers showed that intermittent photic stimulation at 10 Hz could externally induce a coherent state in the cortex and persist as a form of short memory [19]. Milone's group showed that a 10 Hz red light-emitting diode (650 nm) light, consistent with the alpha rhythms, gives rise to cognitive function and regulatory function in the brain [20]. Specific brainwaves and functions of the brain can be induced with different kinds of light stimulations.…”
Section: Light Stimulation and Eegmentioning
confidence: 99%